Nilai-Nilai Budaya Dalam Novel 99 Cahaya Di Langit Eropa Karya Hanum Salsabiela Rais - Julita, Dela; Yuniati, Ira; Elyusra, Elyusra; Gunawan, Hafiz (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This study aims to describe the cultural values contained in the novel 99 light in the sky of Europe by Hanum Salsabiela Rais. The method used is descriptive analysis with a qualitative approach. Research Data in the form of quotations from the novel that contains cultural values. The main data source is the novel 99 lights in the European Sky, published by PT. Gramedia Pustaka Utama, Jakarta, with 420 pages thick and published in November 2013. Data collection techniques used are literature studies, while data analysis is done by content analysis method. To ensure the validity of the data, the techniques of extension of participation, persistence of observations, detailed description and auditing are used. The results showed that there are various kinds of cultural values that are divided into three categories, namely human relations with oneself (consisting of 22 quotes), human relations with other humans (23 quotes), and human relations with God (20 quotes that are divided into 4 aspects). For further research, it is recommended that further studies be carried out on other aspects of cultural values in the novel in order to contribute ideas to students, especially in the field of literature.